UPAYA GURU DALAM MENGATASI KESULITAN LITERASI BACA TULIS SISWA KELAS I SD NEGERI 186/I SRIDADI - Sari, Maya Sari; Syarif, Ahmad; Budiono, Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe students’ difficulties in reading and writing literacy, the inhibiting factors, and teachers’ efforts to overcome reading and writing literacy difficulties among first-grade students at SD Negeri 186/I Sridadi. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation, while data analysis consisted of data reduction, data presentation, and conclusion drawing, with triangulation techniques used to ensure data validity. The results showed that reading literacy difficulties included letter recognition, distinguishing letters with similar shapes and sounds, blending syllables, and reading fluency, while writing literacy difficulties included inaccurate letter formation, inappropriate use of capital letters, irregular spacing between letters and words, and untidy handwriting. The inhibiting factors of reading and writing literacy difficulties originated from students’ internal factors, family environment, and lack of practice at home. Teachers’ efforts to address these difficulties included step-by-step instruction, the use of instructional media, individual guidance, providing correct reading and writing models, and the implementation of school literacy programs.